The succinylome of Pinctada fucata martensii implicates lysine succinylation in the allograft-induced stress response. Issue 127 (August 2022) - Zhang, Meizhen; Lu, Jinzhao; Liang, Haiying; Zhang, Bin; Liang, Bidan; Zou, Hexin
Abstract: Lysine succinylation is a novel protein post-translational modification associated with the regulation of a variety of cellular processes. Post-translational modifications may regulate the immune response of Pinctada fucata martensii, a marine bivalve used to produce cultured pearls, in response to the surgical implantation of the seed pearl. This allograft-induced stress response may lead to transplant rejection or host death. However, the regulatory effects of post-translational modifications following nucleus insertion surgery in P.f. martensii remain largely unknown. Here, we used 4D label-free quantitative proteomics (4D-LFQ) with LC-MS/MS to explore the effects of nucleus implantation on lysine succinylation in P.f. martensii . We identified 4430 succinylated sites on 964 succinylated proteins in P.f. martensii after nucleus insertion surgery, and seven conserved motifs were identified upstream and downstream of these sites. In total, 269 succinylation sites were differentially expressed in response to implantation (|fold-change| > 1.5 and FDR <1%; 211 upregulation and 58 downregulation), corresponding to 163 differentially expressed succinylated proteins (DESPs; 124 upregulated and 39 downregulated). The terms over-enriched in the DESPs included "cellular processes", "metabolic pathways", and "binding activity", while the significantly enriched pathways included "ECM-receptor interaction", "PI3K-Akt signaling", and "focal adhesion". "EGF-like structural domains", "platelet-responsive protein type 1 structural domains", and "laminin EGF-like (domains III and V) domains" were overrepresented in the DESPs. Parallel reaction-monitoring (PRM) analysis validated 13 DESPs from the proteomics data. The succinylome of P.f. martensii (generated here for the first time) helps to clarify the biological role of large-scale succinylation in this bivalve after nucleus insertion surgery, providing a theoretical basis for further investigations of stress-induced post-translational modifications in other mollusks and extending our knowledge of the molluscan succinylated proteome. Highlights: Allograft-induced succinylation proteomic was first studied in Pinctada fucata martensii. A variety of differentially expressed succinylated proteins (DESPs) were responsive to nucleus implantation. DESPs were associated with "immune system processes" and "the response to stimulus". "ECM-receptor interaction pathway" was enriched in succinylation proteomic.